The International Liaison Committee on Resuscitation—Review of the last 25 years and vision for the future. (December 2017) - Perkins, Gavin D.; Neumar, Robert; Monsieurs, Koenraad G.; Lim, Swee Han; Castren, Maaret; Nolan, Jerry P.; Nadkarni, Vinay; Montgomery, Bill; Steen, Petter; Cummins, Richard; Chamberlain, Douglas; Aickin, Richard; et al.
Abstract: 2017 marks the 25th anniversary of the International Liaison Committee on Resuscitation (ILCOR). ILCOR was formed in 1992 to create a forum for collaboration among principal resuscitation councils worldwide. Since then, ILCOR has established and distinguished itself for its pioneering vision and leadership in resuscitation science. By systematically assessing the evidence for resuscitation standards and guidelines and by identifying national and regional differences, ILCOR reached consensus on international resuscitation guidelines in 2000, and on international science and treatment recommendations in 2005, 2010 and 2015. However, local variation and contextualization of guidelines are evident by subtle differences in regional and national resuscitation guidelines. ILCOR's efforts to date have enhanced international cooperation, and progressively more transparent and systematic collection and analysis of pertinent scientific evidence. Going forward, this sets the stage for ILCOR to pursue its vision to save more lives globally through resuscitation.